DEVELOPMENT OF CONSTRUCTIVIST-BASED STUDENT WORKSHEETS ON BASIC MANAGEMENT COMPETENCIES IN CLASS X AT TERENAM NEGERI HIGH SCHOOL 2 SEMBAWA - RAMBOKU, ANODIET (EDUCATE, 2025)
The Entitled Research on Development of Constructivist Based Student Worksheets in Basic Management Competencies in Class X in Sembawa State Senior High School 2 aims to produce Constructivistic Based Student Worksheets in valid and practical Management Basic Competencies and have the effectiveness of student learning outcomes in Schools. Upper middle class. This research method uses development research using the Rowntree Tesmer model development model. This research through a phase consisting of three stages, namely the planning stage, the development stage, and the evaluation phase. LKPD is based on constructivist management material, from the results of expert review assessment obtained from media experts, material experts, and learning design experts, with very valid categories, from the results of One to One test obtained in very practical categories. Constructivist based LKPD management materials can be used in creative and innovative learning processes. Constructivist based LKPD management material developed, from the results of the Small group test categorized as very practical so that it can be used in the learning process and improve students' understanding of the concept of learning. Constructivist-based LKPD developed has effectiveness on student learning outcomes. This can be seen from the results of the posttest of students at the product trial stage in the field. The average student learning outcomes at pretest are very low while the average student learning outcomes at the posttest has increased after learning using LKPD based on constructivist management material and obtained N-gain which is categorized as medium. Based on the results of the research that has been done, the suggestions that can be given are as follows. For Educators, it is hoped that constructivist-based LKPD teaching materials produced can be used as one of the teaching materials that facilitate the delivery of subject matter, and as an effort to improve learning so that creative and innovative learning is created. For schools, it is hoped that constructivist-based LKPD teaching materials can be used in the learning process and can improve student learning outcomes, For students, it is recommended that students use constructivist-based LKPD this management material as teaching material in the learning process so as to improve students' understanding of the concept of learning and for other researchers, expected to be able to develop LKPD constructivist based on other material and can be validated by constructivist experts